2015
DOI: 10.1021/acs.jcim.5b00538
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Binding Free Energy Predictions in Fragment Optimization

Abstract: Predicting protein-ligand binding free energies is a central aim of computational structure-based drug design (SBDD)--improved accuracy in binding free energy predictions could significantly reduce costs and accelerate project timelines in lead discovery and optimization. The recent development and validation of advanced free energy calculation methods represents a major step toward this goal. Accurately predicting the relative binding free energy changes of modifications to ligands is especially valuable in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
194
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(213 citation statements)
references
References 81 publications
16
194
0
3
Order By: Relevance
“…The lower correlation with experiment obtained for two series of adenine-derived ligands may reflect that these were of lead-like size and interacted with the flexible extracellular loops whereas the fragments considered in this work had limited conformational flexibility and extended into a relatively rigid TM region. Interestingly, two recent benchmarks of binding free energy calculations for a large number of soluble targets showed a similar trend 10, 39 . It should be noted that access to information regarding the binding mode for a representative ligand was likely a key contributor to the accuracy of the MD/FEP calculations in all cases.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The lower correlation with experiment obtained for two series of adenine-derived ligands may reflect that these were of lead-like size and interacted with the flexible extracellular loops whereas the fragments considered in this work had limited conformational flexibility and extended into a relatively rigid TM region. Interestingly, two recent benchmarks of binding free energy calculations for a large number of soluble targets showed a similar trend 10, 39 . It should be noted that access to information regarding the binding mode for a representative ligand was likely a key contributor to the accuracy of the MD/FEP calculations in all cases.…”
Section: Discussionmentioning
confidence: 69%
“…In either case, access to high-resolution crystal structures of fragments bound to the target often makes crucial contributions to the optimization process 7 . Whereas computational methods for structure-based ligand design are routinely used for drug-sized molecules 9 , applications of such approaches to fragment optimization have been more scarce 10 . The fact that fragments are weak ligands, only occupy a small fraction of the binding site, and may have multiple binding modes adds extra levels of complexity that are challenging to predict with simplified models such as empirical scoring functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS λ D has historically focused on modifying small functional groups. 6,7,20 While such calculations have many applications, the ability to look at larger perturbations with landscape flattening opens up new possibilities in fragment-based drug design 13,36 and in exploring the effects of protein mutation on drug binding. 37–39 …”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage of simulations is their computational cost, which prohibits the possibility of performing screening studies with MD simulations. This might change in the future, as a recent example using MD methods in fragmentbased drug design has demonstrated that MD might be possible for screening studies [10]. This review will provide a brief overview of the most common experimental techniques applied in the study of drug-membrane interactions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%